An analytical study about Sport School and its role in developing learning motivation among midle School students in the state of Ain Defla - Benhadj Djilali, Smail; Bourzama , Daoued; Benhadj Taher, abdelkader (sports creativity, 2025)
Our research aims to know the role of school sport in increasing the learning motivation of middle school pupils, as we assumed that school sport contributes to increasing the motivation of learning and intends to ensure the validity of the general hypothesis. The field was based on a sample consisting of (120) male and female students, distributed evenly between practicing and non-practicing pupils, and the sample represented four averages from the city of Ain Defla, and after collecting and unpacking the data we used the difference evidence test (T) to compare the results of the pupils that were in favor of the practicing pupils. School sports work to increase interest and desire for education and to develop a positive attitude towards school. It also increases self-confidence and exerts extra effort through perseverance and organization in the learning process.